Numerical Study for Predicting The Initial Flash Point in Geothermal Wellbore: an Euler-Cauchy Method Approach - Hasisi, Subhan; Khasani, Khasani (Riviera Publishing, 2025)
The precise forecasting of the initial flash point in geothermal wellbore is a crucial determinant for characterizing two-phase flow dynamics, the initiation of scaling, and overall well productivity. Despite the prevalence of considerable dissolved CO? in numerous geothermal reservoirs, prevailing wellbore simulators frequently overlook the thermodynamic interactions between CO? and H?O. This study introduces a one-dimensional Euler–Cauchy numerical model founded on the conservation laws of mass, momentum, and energy, which is coupled with a thermodynamic framework that explicitly accounts for CO?. This framework incorporates CO? solubility, vapor-liquid equilibrium, and the corresponding variations in mixture properties. A parametric analysis was conducted across CO? mass fractions of 0.00% to 1.00%. The simulations reveal that increased CO? concentrations displace the flash point to greater depths within the wellbore, that were 1409.5m depth, 1312m, 1233m, 1174m and 1134 for 1.00% CO?, 0.75%, 0.50%, 0.25% and 0.00% respectively. These results underscore the significant impact of non-condensable gases on geothermal well performance and provide critical insights for managing scale formation, mitigating corrosion, and optimizing operations.